(untitled) (Research, Society and Development, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is considered a common preschool disorder, affecting 5 to 8% of the world’s child population. The theme is relevant in the educational area, which is closely related to it, contributing to the clarification of concepts, symptoms and description of the disorder. Regarding the legislation, the current one did not specify clearly on the subject, which is theoretically understood in special educational needs. However, in November 2021, the new Law No. 14,254 was published, which objectively deals with the subject, bringing new guidelines. From this perspective, the study aims to analyze concepts and interpretations about ADHD, ADHD and Education, the previous legislation on the subject and the new guidelines. For this purpose, a qualitative methodology was used in this study, in relation to the objectives, exploratory and descriptive, as it seeks to explore concepts, meanings and classifications of ADHD in different authors and perspectives and, for the procedures, bibliographic. The research was carried out in a virtual environment, in reliable databases such as Scielo, with scientific articles and books in pdf format, publications and current legislation, with the descriptors ADHD, new guidelines, legislation, education. Which resulted in a discussion organized into four topics, of which: e ADHD, ADHD and education, ADHD and legislation and New guidelines for ADHD. The author’s conclusions and impressions can be found in the final considerations.